Early and Late Effects of Cardiac Resynchronization Therapy in Adult Congenital Heart Disease. Issue 21 (5th November 2019) - Yin, Yanrong; Dimopoulos, Konstantinos; Shimada, Eriko; Lascelles, Karen; Griffiths, Samuel; Wong, Tom; Gatzoulis, Michael A.; Babu‐Narayan, Sonya V.; Li, Wei
Abstract : Background: There are limited data about cardiac resynchronization therapy (CRT) in adult congenital heart disease. We aimed to assess early and late outcomes of CRT among patients with adult congenital heart disease. Methods and Results: We retrospectively studied 54 patients with adult congenital heart disease (median age, 46 years; range, 18–73 years; 74% men) who received CRT implantation (biventricular paced >90%) between 2004 and 2017. Clinical and echocardiographic data were analyzed at baseline and early (mean±SD: 1.8±0.8 years) and late (4.7±0.8 years) follow‐up after CRT. Compared with baseline, CRT was associated with significant improvement at early follow‐up in New York Heart Association functional class, QRS duration, and cardiothoracic ratio ( P <0.05 for all); improvement in New York Heart Association class was sustained at late follow‐up. Among patients with a systemic left ventricle (LV; n=39), there was significant increase in LV ejection fraction and reduction in LV end‐systolic volume at early and late follow‐up ( P <0.05 for both). For patients with a systemic right ventricle (n=15), there was a significant early but not late reduction in systemic right ventricular basal and longitudinal diameters. Eleven patients died, and 2 had heart transplantation unrelated to systemic ventricular morphological characteristics. Thirty‐five patients (65%) responded positively to CRT, but only baseline QRS duration was predictive of a positive response. Conclusions: CRT results in sustained improvement in functional class, systemic LV size, and function. Patients with a systemic LV and prolonged QRS duration, independent of QRS morphological characteristics, were most likely to respond to CRT.